2020
DOI: 10.22159/ijpps.2020v12i3.36518
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Methanolic Extract of Sargassum Wightii on Haloperidol Induced Catalepsy and Tardive Dyskinesia in Albino Rats

Abstract: Objective: The present study was designed to evaluate the neuroprotective effect of methanolic extract of Sargassum wightii on haloperidolinduced catalepsy and tardive dyskinesia in Wistar albino rats. Methods:In this study, thirty Wistar albino rats were randomly divided into six groups. Gr-I served as control. Haloperidol (1 mg/kg intraperitoneally) was administered to rats of Gr-II to Gr-V for twenty-one consecutive days to induce catalepsy and tardive dyskinesia. Animals of Gr-II to Gr-V were orally admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The animals were observed for 24 hours. No mortality or behavioral changes were observed during the study period (16).…”
Section: Acute Toxicity Testmentioning
confidence: 92%
See 1 more Smart Citation
“…The animals were observed for 24 hours. No mortality or behavioral changes were observed during the study period (16).…”
Section: Acute Toxicity Testmentioning
confidence: 92%
“…The methanolic extract of S. wightii was subjected to a phytochemical screening test in our earlier study and was found to contain polyphenols, terpenoids, tannins, flavonoids, and polysaccharides (16).…”
Section: Phytochemical Screening Of Plant Extractmentioning
confidence: 99%
“…of 1 for each paw was added to the scores of steps I and II. Thus, the highest score for any animal was 3.5 (cut off score) and that reflects total catalepsy [31,32].…”
Section: Bala and Abidmentioning
confidence: 99%
“…Polyphenolic compounds like flavonoids present in marine macro algae being potent antioxidants. The antioxidant, anti-inflammatory and neuroprotective effects of Sargassum wightii were well established [7,8]. But there is paucity of data regarding neuroprotective effect of Sargassum wightii especially of Indian coasts origin.…”
Section: Introductionmentioning
confidence: 99%